Spatial Distributions of Job Accessibility, Housing Rents, and Poverty in Nairobi, Kenya - Nakamura, Shohei; Avner, Paolo (World Bank, Washington, DC, 2018)
Whether individuals and job opportunities are well connected is a key determinant of productive urban labor markets. The overall level of job accessibility in a city depends on the locations of jobs and workers' residences, as well as transport networks. Moreover, who has good access to job opportunities hinges on the trade-off faced by households in their residential choices over job accessibility, living conditions, and housing costs. This paper empirically analyzes the spatial distributions of job accessibility, housing rents, and poverty in Nairobi, Kenya. It finds that workers and jobs are not well connected in the city: Nairobi residents can on average access fewer than 10 percent of existing jobs by foot within an hour. Even using a minibus, they can reach only about a quarter of the jobs. This paper further shows that poorer households and/or those who live in informal settlements can reach a more limited number of jobs. Living closer to job opportunities is indeed costly in Nairobi, not only because housing quality and living conditions tend to be better in such areas, but also job accessibility itself is valued as a great amenity in the housing markets, which challenges low-income households' residential location choice.